An Islamic Model Of Conflict Management And Conflict Resolution: Lahad Datu In Sabah As A Case Study - Ahmed Abdul Malik; Najib Sheikh Abdisamad; Muhammad Khairi Mahyuddin; Mikail Ibrahim (De Gruyter Open, 2024)
Conflict is an inevitable part of human life. In any situation involving more than one person, conflict can arise. The causes of conflict range from philosophical differences and divergent goals, to power imbalances. When conflict arises, it is easy for people to be stubborn and remain entrenched in their positions and for tempers to flare, voices to rise and body language to become defensive or aggressive. Conflict is an unexpected inconvenience. This can be proved by the Lahad Datu Sabah conflict which occurred in 2013, where armed men landed in Lahad Datu to enforce an ancestral land claim. During the conflict, 12 security police were killed and some of them were mutilated. A week-long impasse in a coastal village ended in bloodshed, as a Malaysian ground assault gave way to air strikes. The aims of this research is to analyze the issues of Lahad Datu, to examine the strategies that can be used to promote peace and stability and to introduce an Islamic model of conflict resolution. A self-constructed survey instrument was distributed to 236 residents of Lahad Datu, who voluntarily participated in the study. The results indicated that a level of awareness and a resolution of conflict effects peoples reaction towards a governments response to invaders, their perceptions about the causes of the conflict and their stance during a conflict. Furthermore, the study found that gender, religion, education, occupation and marital status had no effect on the dependent variables. Finally, the findings of the research disclosed that an Islamic model of conflict resolution can be used to resolve the conflict of Lahad Datu or similar social conflicts.